THE INFLUENCE OF FASHION INVOLVEMENT, POSITIVE EMOTIONS AND AFFILIATE MARKETING ON IMPULSE BUYING GENERATION Z (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
This research aims to determine: (1) the joint influence of fashion involvement, positive emotions and affiliate marketing to impulse buying on generation Z users of the Shopee application in Yogyakarta City, (2) influence fashion involvement to impulse buying among generation Z users of the Shopee application in Yogyakarta City. (3) the influence of positive emotions on impulse buying on generation Z users of the Shopee application in Yogyakarta City, (4) influence of affiliate marketing to impulse buying among generation Z users of the Shopee application in Yogyakarta City. The sampling technique used is purposive sampling. Data was obtained by distributing questionnaires about fashion involvement, positive emotions, affiliate marketing and impulse buying to 100 respondents. Data analysis using multiple linear regression and using SPSS 22. The research results showed that: (1) fashion involvement, positive emotions, affiliate marketing together have a significant effect on impulse buying, (2) fashion involvement positive and significant effect on impulse buying, (3) positive emotions have a positive and significant effect on impulse buying, (4) affiliate marketing positive and significant effect on impulse buying.
Keywords: Fashion Involvement; Positive Emotions; Affiliate Marketing; Impulse Buying